Effectiveness of Laboratory Physical Modeling in Acquiring the Response of Time Domain Induced Polarization (TDIP) - Y Yatini; Djoko Santoso; Agus Laesanpura; Budi Sulistijo (Universitas Negeri Surabaya, 2022)
Induced Polarization (IP) is one of the Geophysical methods that utilize the polarization properties of the rocks for metallic mineral exploration. The problems are how to distinguish the metallic minerals deposit based on the chargeability. The physical modeling of IP is used to study the behavior of TDIP response. The study of a simple mathematical model is carried out to obtain the theoretical curves which are presented as the subsurface parameter. These curves are used as a reference to assess the result of physical modeling. The laboratory physical modeling uses a tank model with a size of (200x100x70) cm3, with a block as a target and water as a host medium. The results show laboratory physical modeling which has been made is quietly good. The approximate position and geometry of the target can be identified. The resistivity inversion modeling is sensitive to recognizing the geometry and position, while the chargeability inversion is on the distribution of metallic minerals. The quantitative correlation between chargeability and iron-ore content is obtained by Dipole-dipole and Wenner configuration. Both are connected exponentially, with a different exponential constant for different block targets.